Nurses’ perspectives on readiness of organizations for change: a comparative study - Amarneh BH (Dove Medical Press, 2017)
Basil Hameed Amarneh Department of Psychiatric and Community Health Nursing, Faculty of Nursing, Jordan University of Science and Technology, Irbid, Jordan Purpose: The purpose of this study is to evaluate readiness for change perceived by nurses at Jordanian hospitals according to the hospital type and the gender of nurse.Background: There are misconceptions about readiness for change, and only a few health care and nursing studies about organizational readiness for change have been conducted. Nurses’ perceptions of their organizations’ readiness for change are important; they help in introducing, managing, and maintaining the change.Methods: Using a quantitative comparative research design and a validated survey, data were collected in 2010 from a convenience sample of 130 nurses from four government and three private hospitals with a response rate of 59%.Results: There are some issues in Jordanian hospitals, which show that change has to be managed well. Nurses in government hospitals and female nurses perceived their hospitals to be more ready for change, compared with those in private hospitals and male nurses.Conclusion: Government hospitals were more ready to change than private hospitals, particularly in supporting collaborative and multidisciplinary team approaches to patient care. More than male nurses, female nurses perceived that their organizations were ready to use or plan to use advanced practice nurses. One of the recommendations is a need for targeted intervention to improve readiness for change. Keywords: readiness for change, organizations, hospitals, nurses, Jordan